Clinical Characteristics and Surgical Modality of Plasma Cell Mastitis: Analysis of 91 Cases. Issue 1 (January 2013) - Ming, Jia; Meng, Gang; Yuan, Qiaoying; Zhong, Ling; Tang, Peng; Zhang, Kongyong; Chen, Qingqiu; Fan, Linjun; Jiang, Jun
The objective of this study was to investigate the clinical characteristics and surgical modality of plasma cell mastitis (PCM). A total of 93 breasts of 91 female patients with PCM from June 2003 to June 2010 (unilateral in 89 patients and bilateral in two patients) were investigated in this study. All breasts were divided into two groups: the direct excision group (DE group) received focused excision and nipple retraction correction; and the incision drainage group (ID group) received these procedures only in the event of failing at least two incision drainages. Clinical characteristics, extent of excision, and prognosis were compared between two groups. There were 53 breasts in the DE group and 40 breasts in the ID group. No significant differences were noted in the number of retracted nipples and abscesses in the first visit or extent of disease between two groups ( P > 0.05). However, during surgery, 3.85 ± 0.97 abscesses per breast were detectable in the ID group, which was significantly higher than 1.21 ± 0.06 abscesses per breast in the DE group. The ID group had significantly higher inflammation and excised extent compared with the DE group ( P < 0.05). Hospitalization time was 179.60 ± 14.8 days in the ID group, which was significantly higher than 22.49 ± 1.93 days in the DE group ( P < 0.05). Bacterial culture was negative for pus of 39 non-rupturing abscesses. Congenital nipple retraction may be the primary cause of PCM. Early and complete focused excision and nipple retraction correction are effective treatment methods.